FACTORS RELATED TO HIV / AIDS PREVENTION EFFORTS IN SENIOR HIGH SCHOOL STUDENTS CLASS X, 8 BANDA ACEH - Husna, Asmaul (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2017)
According to the data from the Ministry of Health (2012) from January to December of 2012, the number of HIV cases in Indonesia as many as 21,511 cases and AIDS as many as 5,686 cases spread in 386 of 498 districts / cities in all provinces in Indonesia, with the most cases coming from Papua Province. According to cumulative data of most cases of HIV / AIDS at the age of 20-29 years as many as 45.4% and the lowest at age 40-49 years as much as 9.9%, with the most risk factors are through heterosexual. The purpose of this study was to determine factors related to HIV / AIDS prevention efforts in Grade X students of SMA Negeri 8 Banda Aceh. Population in this research is all class X student in senior high school 8 Banda Aceh which amounts 244 which is divided into 8 classes. This study has been conducted from 18 November to 23 November 2016. The sample is part or representative of the studied poll. The sample in this study is the total sampling (total sampling) that is all students in high school class X in senior high school 8 Banda Aceh as many as 244 students. Results of bivariate analysis There is a correlation between knowledge with HIV / AIDS prevention effort In senior high school 8 Banda Aceh students, p-value = 0,008 (p <0,05), There is relationship between information with HIV / AIDS prevention at senior high school 8 Banda Aceh, obtained p-value = 0,007 (p <0,05). The conclusion of the research is as follows: There is a correlation between knowledge with HIV / AIDS prevention efforts In SMA Negeri 8 Banda Aceh students, obtained p-value = 0.008 (p <0.05), There is a relationship between information with HIV / AIDS prevention efforts In SMA Negeri 8 Banda Aceh students, obtained p-value = 0,007 (p <0,05).keywords : knowledge, information